Identifying Effective Factors on Educational Reform at the Level of National and Regional Supports for High School Mathematics - Ziyaei, Maryam; Keshtiaray, Narges; Kashefi, Hamidreza (Iranian Journal of Educational Sociology, 2022)
Purpose: This research was conducted with the aim of identifying effective factors on educational reform at the level of national and regional supports for high school mathematics.Methodology: The present study in terms of purpose was applied and in terms of implementation method was qualitative, which was performed in two stages of synthesis research and content analysis. The research environment in the synthesis research stage were all reference texts about recognizing the needs of the high school mathematics curriculum in the period of 2007 to 2020 years, which number of 47 sources were selected as a sample by purposeful sampling method. The research environment in the content analysis stage were all reference texts of educational reform of the high school mathematics curriculum and national and regional support in the period of 2010 to 2020 years, which number of 7 sources were selected as a sample by purposeful sampling method. The content validity of the data was confirmed by 5 experts in the field of curriculum and education of mathematics and their reliability was obtained by the agreement coefficient method between the two coders 0.88. Data were analyzed by synthesis research and content analysis methods via deductive.Findings: The results of synthesis research showed that for the effective factors on educational reform were identified 5 components and 12 subcomponents, which the components included the need to review the curriculum, preparation of teachers to change the curriculum, the need for teacher training, supervision of the education system on the teachers' performance and providing curriculum implementation arrangements. Also, the results of content analysis showed that for the effective factors on educational reform were identified 2 components and 7 subcomponents, which the components included preparation teachers to change the curriculum and providing curriculum implementation arrangements. Finally, the diagram of the effective factors on educational reform at the level of national and regional supports for high school mathematics was drawn.Conclusion: According to the results of this study, planning to improve the education of high school mathematics is essential through the use of effective factors on educational reform.